Research Commentary: Rethinking “Diversity” in Information Systems Research - Benbasat, Izak; Weber, Ron (Information Systems Research, 1996)
Three types of diversity have been prominent in the Information Systems discipline for over a decade: (a) diversity in the problems addressed; (b) diversity in the theoretical foundations and reference disciplines used to account for IS phenomena; and (c) diversity in the methods used to collect, analyze, and interpret data. History has played a major part in encouraging IS researchers to use diversity as a means of countering criticisms of their discipline and increasing their research rigor and productivity. In particular, frequent recourse to reference disciplines has underpinned much of the research that has been undertaken since the early 1980s. There are now signs, however, that the level of diversity that currently exists in IS research may be problematic. In this paper, we consider some of the benefits and costs of allowing diversity to reign in the IS discipline. We also propose a structure that we hope will facilitate discourse on the benefits and costs of diversity and on the role that diversity should now play in the IS discipline.